Implementation of records management practices in technical and vocational education and training institutions in South Africa - Kodisang, Mmamie Evelyn (Department of Knowledge and Information Stewardship, 2025)
In technical vocational education and training colleges, records management plays a major role as it enables service delivery in a consistent, equitable manner, and it further provides continuity and productivity in its management and administration. This role extends to the provision of support for the institution's mandate, that of research, teaching, learning, and community engagement. Despite the crucial role that records play in TVET institutions, several studies have highlighted a lack of appreciation for this role. In this context, the study was undertaken to explore implementing records management practices in a TVET institution. The Organisational Culture Framework by Schein and Schein (2016) was determined to be an appropriate framework supporting the study due to the connection between records and information management. To optimise the theoretical implications of research findings, a case study research design was employed. To allow the researcher to develop the meaning of a situation, constructivism was chosen as the appropriate worldview for the study. Qualitative data collection was used for both administrators and managers using semi structured physical questionnaires and face-to-face semi-structured interviews, respectively. A purposeful sample of 17 administrators and 21 managers was used. The key findings of the study revealed that administrative staff lacked formal records management training. Additionally, there is limited funding for training staff on records management. Moreover, there are no policies on records management. Based on the findings, the study recommends the need for trained records management staff paired with records management governance guidelines, as well as management buy-in, and records management being driven from the top. The study concluded that for records management to be fully implemented, management should ensure that records management staff are trained on records management principles and provided with guidelines, including infrastructure. To make this possible, the study recommended that senior management make funds available to train records management staff on records management principles. In addition, senior management must make records management governing documents available and use their authority to compel staff to comply with these policies.